Effectiveness of Two Targeted Temperature Management Methods After Pediatric Postcardiac Arrest: A Multicenter International Study*. Issue 2 (February 2019) - Yunge, Mauricio; Cordero, Jaime; Martinez, Daniela; Bustos, Raul; Wegner, Adriana; Castro, Magdalena; Arrau, Lorena; Diaz, Betsy; Dalmazzo, Roberto; Hickmann, Lilian; Lapadula, Michelangelo; Yañez, Leticia; et al.
Abstract : Objectives: It is currently recommended that after return of spontaneous circulation following cardiac arrest, fever should be prevented using TTM through a servo-controlled system. This technology is not yet available in many global settings, where manual physical measures without servo-control is the only option. Our aim was to compare feasibility, safety and quality assurance of servo-controlled system versus no servo-controlled system cooling, TTM protocols for cooling, maintenance and rewarming following return of spontaneous circulation after cardiac arrest in children. Design: Prospective, multicenter, nonrandomized, study. Setting: PICUs of 20 hospitals in South America, Spain, and Italy, 2012–2014. Patients: Under 18 years old with a cardiac arrest longer than 2 minutes, in coma and surviving to PICU admission requiring mechanical ventilation were included. Methods: TTM to 32–34°C was performed by prospectively designed protocol across 20 centers, with either servo-controlled system or no servo-controlled system methods, depending on servo-controlled system availability. We analyzed clinical data, cardiac arrest, temperature, mechanical ventilation duration, length of hospitalization, complications, survival, and neurologic outcomes at 6 months. Primary outcome: feasibility, safety and quality assurance of the cooling technique and secondary outcome: survival and Pediatric Cerebral Performance Category at 6 months. Measurements and Main Results: Seventy patients were recruited, 51 of 70 TTM (72.8%) with servo-controlled system. TTM induction, maintenance, and rewarming were feasible in both groups. Servo-controlled system was more effective than no servo-controlled system in maintaining TTM (69 vs 60%; p = 0.004). Servo-controlled system had fewer temperatures above 38.1°C during the 5 days of TTM (0.1% vs 2.9%; p < 0.001). No differences in mortality, complications, length of mechanical ventilation and of stay, or neurologic sequelae were found between the two groups. Conclusions: TTM protocol (for cooling, maintenance and rewarming) following return of spontaneous circulation after cardiac arrest in children was feasible and safe with both servo-controlled system and no servo-controlled system techniques. Achieving, maintaining, and rewarming within protocol targets were more effective with servo-controlled system versus no servo-controlled system techniques.